Environmental protection of springs and groundwater outcrops in Brazil: history and current technical gaps - Souza, Kleber Isaac Silva de (2019)
Even though springs and groundwater outcrops are considered to be permanent preservation area (PPA) since 1965, the legislator, through Law 12651 of 2012, removed the environmental protection of intermittent outcrops. That permanent protection status was reestablished by the Brazilian Federal Supreme Court in February 2018. The knowledge about the new legal interpretation established for the diagnosis and protection of those features by the technical-scientific community is of utmost importance for conducting environmental studies. In this paper we present the historical evolution of environmental protection in the environs of groundwater outcrops in Brazil and its current technical gaps. Two examples show the gaps in the regulatory legislation regarding the precise delimitation of mobile springs and “water eyes” subject to seasonal level variation. Without a clear scientific criteria, the precise delimitation of this modality of PPA might be compromised. It is hoped that this paper will encourage future work to investigate solutions that contribute to improving the protection and restoration of water-related ecosystems.